Top-down vs. bottom-up: The long-term impact of government ideology and personal experience on values - Nicolas Ziebarth; Gert G. Wagner (Institute for the Study of Labor (IZA), 2013)
This paper studies the long-term impact of societal socialization on values using the example of doping behavior in sports. We apply the German Reunification Approach to the microcosm of Berlin and exploit its 40-year long division into a capitalist and a communist sector. We deliberately chose attitudes toward doping to test the impact of ideology on values since (i) post-1989 disappointed economic hopes did not confound doping attitudes, and because of (ii) the systematic GDR state doping activities that became public in reunified Germany in the 1990s. Our findings demonstrate that even after half the time the division lasted, e.g. 20 years after the reunification, differences in convictions continue to persist. Personal extramural sports experience and age are equally strong predictors of individual attitudes and beliefs, especially in interaction with ideological socialization.
Keywords: I18; K40; L83; N34; Z13; 330; communism; values; performance-enhancement drugs; Berlin; natural experiment